Nongenetic Approach for Imaging Protein Dimerization by Aptamer Recognition and Proximity-Induced DNA Assembly - Liang, Hong; Chen, Shan; Li, Peipei; Wang, Liping; Li, Jingying; Li, Juan; Yang, Huang-Hao; Tan, Weihong (Journal of the American Chemical Society, 2018)
Herein, we report a nongenetic and real-time approach for imaging protein dimerization on living cell surfaces by aptamer recognition and proximity-induced DNA assembly. We use the aptamer specific for the receptor monomer as a recognition probe. When receptor dimerization occurs, the dimeric receptors bring two aptamer probes into close proximity, thereby triggering dynamic DNA assembly. The proposed approach was successfully applied to visualize dimerization of Met receptor and transforming growth factor-β type II receptor. This approach allows us to image the two states (monomer/dimer) of a receptor protein on living cell surfaces in real time, opening a universal method for further investigation of protein dimerization and the corresponding activation processes in signal transduction.